2019 Global food policy report - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s flagship report reviews the major food policy issues, developments, and decisions of 2018, and considers challenges and opportunities for 2019. This year’s Global Food Policy Report highlights the urgency of rural revitalization to address a growing crisis in rural areas. Rural people around the world continue to struggle with food insecurity, persistent poverty and inequality, and environmental degradation. Policies, institutions, and investments that take advantage of new opportunities and technologies, increase access to basic services, create more and better rural jobs, foster gender equality, and restore the environment can make rural areas vibrant and healthy places to live and work. Drawing on recent findings, IFPRI researchers and other distinguished food policy experts consider critical aspects of rural revitalization.